Limited value of pulse wave analysis in assessing arterial wave reflection and stiffness in the pulmonary artery. Issue 18 (23rd September 2021) - Su, Junjing; Simonsen, Ulf; Mellemkjaer, Soren; Howard, Luke S.; Manisty, Charlotte; Hughes, Alun D.
Abstract: We explored the use of the augmentation index (AI) based on pulse wave analysis (PWA) in the pulmonary circulation as a measure of wave reflection and arterial stiffness in individuals with and without pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). Right heart catheterization was performed using a pressure and Doppler flow sensor–tipped catheter to obtain simultaneous pressure and flow velocity measurements in the pulmonary artery in 10 controls, 11 PAH patients, and 11 CTEPH patients. PWA was applied to the measured pressure, while wave intensity analysis (WIA) and wave separation analysis (WSA) were performed using both the pressure and velocity to determine the magnitudes and timings of reflected waves. Type C (AI < 0) pressure waveform dominated in controls and type A (AI > 12%) waveform dominated in PAH patients, while there was a mixture of types A, B, and C among CTEPH patients. AI was greater and the inflection time shorter in CTEPH compared to PAH patients. There was a poor correlation between AI and arterial wave speed as well as measures of wave reflection derived from WIA and WSA. The infection point did not match the timing of the backward compression wave in ~50% of the cases. In patients with type C waveforms, the inflection time correlated well to the timing of the late systolic forward decompression wave caused by ventricular relaxation. In conclusion quantifying pulmonary arterial wave reflection and stiffness using AI based on PWA may be inaccurate and should therefore be discouraged. Abstract : We characterized the pressure waveforms in the pulmonary arteries in individuals with and without pulmonary hypertension. Pulse wave analysis (PWA) is unreliable in the pulmonary circulation due to the challenges related to reliable identification of an inflection point and indices derived from PWA may not be indicative of wave reflection or arterial stiffness, particularly when type C pressure waveforms are common. Assessing wave reflection in the pulmonary artery based on PWA should therefore be discouraged.